Simulated in vitro infant gastrointestinal digestion of yak milk fat globules: A comparison with cow milk fat globules. (1st June 2020) - Luo, Jie; Liu, Lu; Liu, Tianshu; Shen, Qingwu; Liu, Chengguo; Zhou, Hui; Ren, Fazheng
Highlights: Yak milk fat globules were subjected to simulated in vitro infant digestion. Yak milk fat globules were generally more efficiently hydrolyzed than cow milk fat. Yak milk fat globules released more unsaturated fatty acids than cow milk fat. The superior lipid digestion of yak milk lipids was attributed to their lipid properties. Abstract: Lipolysis products released during digestion exert positive metabolic impacts on the nutrition of newborns. However, the lipolysis behavior of yak milk lipids during digestion remains unknown. In this study, the simulated in vitro infant gastrointestinal digestion of cow, yak and standardized yak milk fat globules the same size as those from cow milk (Cow MF, Yak MF and Yak SMF) were compared. Although Cow MF showed a higher lipolysis rate at the beginning of gastric digestion, Yak MF and Yak SMF exhibited a higher lipolysis level during later gastrointestinal digestion. Higher hydrolysis efficiency of yak milk lipids was due to their lipid properties, including their composition and structure. Furthermore, yak milk lipids released more unsaturated fatty acids than Cow MF throughout digestion. This study highlights the crucial role of lipid characteristics in the efficient digestion of milk lipids and provides new insight for the design of yak milk infant diets.